www.fltk.net > 15 8 5x 7x 4 3x

15 8 5x 7x 4 3x

15-8+5x=7x+4-3x 7+5x=3x+4 5x-3x=4-7 2x=-3 x=-1.5

15-(8-5x)=7x+(4-3x) 15-8+5x=7x+4-3x 5x-7x+3x=4+8-15 x=-3

15-8+5x=7x+4-3x 5x-7x+3x=4-15+8 x=-3

1、2x-4–12x+3=9-9x -10x-1=9-9x x= -10 2、9x+64=100-9x 18x=36 x=2 3、15-8+5x=7x+4-3x 7+5x=4x+4 x= -3 4、3x-21-2(9-8+4x)=22 3x-21-2(1+4x)=22 3x-21-2-8x=22 -5x-23=22 -5x=45 x= -9

(1)2(x+15)-21=3x-15 2x+30-21=3x-15 -x=-24 x=24 (2)3(x+8)=5x+8 3x+24=5x+8 2x=-16\x=8 (3)4(x+5*0.8)=7x+5*0.8 4x+16=7x+4 3x=-12 x=-4 (4)x=2*[1.25(x-10)-10] x=2.5(x-10)-20 x=2.5x-45 -1.5x=-45 x=30

1、1-2(2x+3)= -3(2x+1) 1-(4x+6)=-(6x+3) 1-4x-6=-6x-3 6x-4x=-3+6-1 2x=2 x=1

x=5/7,x=15,x=8,x=6,x=1.1,x=2.1,x=2.5,x=5.

①16×8-7x=23, 128-7x=23, 128-7x+7x=23+7x, 128=23+7x, 23+7x-23=128-23, 7x=105, 7x÷7=105÷7, x=15; ②5x+15=60,5x+15-15=60-15, 5x=45, 5x÷5=45÷5, x=9;③3x+x=88, 4x=88, 4x÷4=88÷4, x=22; ④3(x+9)=54,3(x+9)÷3=54÷3, x...

1. 2(x-2)-3(4x-1)=9(1-x) 2. 11x+64-2x=100-9x 3. 15-(8-5x)=7x+(4-3x) 4. 3(x-7)-2[9-4(2-x)]=22 5. 3/2[2/3(1/4x-1)-2]-x=2 6. 2(x-2)+2=x+1 7. 0.4(x-0.2)+1.5=0.7x-0.38 8. 30x-10(10-x)=100 9. 4(x+2)=5(x-2) 10. 120-4(x+5)=25 11. 15x+8...

x=48/5

网站地图

All rights reserved Powered by www.fltk.net

copyright ©right 2010-2021。
www.fltk.net内容来自网络,如有侵犯请联系客服。zhit325@qq.com